Somatic gene variation profiles in geriatric and adult malignant melanoma patients - Ekinci, Busra; Erdogdu, Ibrahim Halil; Orenay-Boyacioglu, Seda; Boyacioglu, Olcay; Kahraman-Cetin, Nesibe; Akin, Dilara; Turan, Merve; Tataroglu, Canten (Frontiers in Oncology, 2025)
IntroductionSkin cancer is a highly heterogeneous disease affecting substantial geriatric individuals. Therefore, understanding gene variants and their presence in geriatric and adult skin cancer patient groups is valuable for the improvement of healthcare policies. The somatic variation profile in geriatric patients diagnosed with malignant melanoma (MM) was examined retrospectively by comparing them to the younger cases to reveal the clinical importance of the panel tests.MethodsThe study included all adult MM patients referred to Molecular Pathology Laboratory from Oncology Clinic between 2019 and 2023. The patients (n = 103) were chronologically divided into geriatric (≥65) and adult (<65 years) groups. The results of targeted next generation sequencing panel studied with probe-capture method were evaluated retrospectively.ResultsAmong the study cohort, 58 (56.31%) were male, 45 (43.69%) were female, and also 55 were in the geriatric age group, 48 were in the adult group with an overall mean age of 63.30 years. The most commonly encountered pathogenic variants in the geriatric MM group were BRAF V600E (14.55%) and V600K (7.27%) variants in Exon 15 followed by NRAS (9.09%), NF1 (9.09%), KIT (5.45%), KRAS (5.45%), CDKN2A (3.64%), and PTEN (3.63%). In the adult MM group, the most common pathogenic variants were BRAF V600E (39.58%) and V600K (8.33%) followed by NRAS (14.58%), NF1 (8.33%), PTEN (8.33%), BRCA2 (8.33%), and TP53 (4.17%).ConclusionsDelineating the distribution of somatic variations in geriatric MM cases holds significant importance in the development of healthcare policies. These data are the first reported findings from Türkiye.